Presenting a Model of Co-Dependency in Women with Addicted Spouses based on their Self-Differentiation with the Mediating Role of Emotional Cognitive Regulation - Karimi Haresabadi, Azam; Mohammadi shirmahaleh, Fatemeh; Rafezi, Zohreh; GholamiTooranposhti, Marziyeh; Peyvandi, Parisa (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to present a model of co-dependency in women with addicted spouses based on their differentiation with the mediating role of emotional cognitive regulation. Methods: The research method is cross-sectional correlation. The statistical population of this study consisted of all women with drug-addicted wives who referred to counseling centers, health centers and addiction treatment camps and meetings in Tehran in 1400, of which 188 people by cluster sampling they were selected in stages. In this study, tools of co-dependency (Span & Fisher, 1990), self-differentiation (Skorn and Friedlander, 1998) and cognitive-emotional regulation (Garnfsky and Craig, 2006) were used. Amos-V8.8 software were used to analyze the data. Structural equation modeling was also used to answer the research hypotheses. Findings showed that the model has a good fit. Results: The results also showed that self-differentiation had a significant direct negative effect on co-dependency (P